2019
DOI: 10.1002/bit.27148
|View full text |Cite
|
Sign up to set email alerts
|

Light‐inducible flux control of triosephosphate isomerase on glycolysis in Escherichia coli

Abstract: An engineering tool for controlling flux distribution on metabolic pathways to an appropriate state is highly desirable in bioproduction. An optogenetic switch, which regulates gene expression by light illumination is an attractive on/off switchable system, and is a promising way for flux control with an external stimulus. We demonstrated a light-inducible flux control between glycolysis and the methylglyoxal (MGO) pathway in Escherichia coli using a CcaS/CcaR system. CcaR is phosphorylated by green light and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Two studies leveraged the CcaRS TCS to redirect the metabolic flux of glycolysis intermediates in E. coli (Senoo et al, 2019;Tandar et al, 2019). In one study (Tandar et al, 2019), the expression of glucose-6-phosphate (G6P) isomerase (GPI) was placed under CcaRS optogenetic control in a gpi knockout strain.…”
Section: Bioproduction and Metabolic Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies leveraged the CcaRS TCS to redirect the metabolic flux of glycolysis intermediates in E. coli (Senoo et al, 2019;Tandar et al, 2019). In one study (Tandar et al, 2019), the expression of glucose-6-phosphate (G6P) isomerase (GPI) was placed under CcaRS optogenetic control in a gpi knockout strain.…”
Section: Bioproduction and Metabolic Engineeringmentioning
confidence: 99%
“…As bioproduction processes often involve the reduction of precursors to less oxidized, desired reaction products, the optogenetically controlled switch between glycolysis and pentose-phosphate pathway may prove widely useful. A second report targeted a step further downstream in glycolysis, namely the reversible interconversion of dihydroxyacetone phosphate (DHAP) and glyceraldehyde-3-phosphate (GAP), as catalyzed by triose-phosphate isomerase (TIM) (Senoo et al, 2019). When put under CcaRS control in a tim knockout background, TIM expression was turned on by green light, and glycolysis proceeded.…”
Section: Bioproduction and Metabolic Engineeringmentioning
confidence: 99%
“…Chemicals or auto-induction systems have been extensively used to achieve flux control, and optogenetics has the potential to perform at least as well as other methods of induction, while also improving controllability. Using the CcaS/CcaR optogenetic system, Senoo et al [38] (Figure 1d) and Tandar et al [39] controlled the expression of the tpiA and pgi genes, respectively, two important genes that channel metabolite flux towards glycolysis in E. coli. Both studies demonstrated enrichment in their respective competing pathways, as expected.…”
Section: Simple Switch For Flux Rewiringmentioning
confidence: 99%
“…Optogenetics has already been applied to bioproduction, though only in a handful of lab-scale studies. Light has mostly been used to control transcription irreversibly ( Raghavan et al, 2020 ) or reversibly ( Zhao et al, 2018 ; Senoo et al, 2019 ; Ding et al, 2020 ; Lalwani et al, 2020 ), to direct the assembly of enzymatic clusters ( Zhao et al, 2019 ), or to tune the composition of microbial consortia ( Lalwani et al, 2021b ). Development of an optogenetic producer strain at the lab-scale requires the use of specific illumination devices.…”
Section: Introductionmentioning
confidence: 99%